THE USE OF PICTURES SERIES IN IMPROVING STUDENTS' WRITING PROCEDURAL TEXT: Quasi Experimental Study of Seventh Grade Students at One Junior High School in Bandung) - Setiawan, Jaka (2014)
This research paper entitled "The Use of Picture Series in Improving Students' Writing Procedural Text" was intended to test the effectiveness of using pictures series to improve students' writing skill especially writing procedural text. The Participants in this study were seventh grade students at one Junior High School in Bandung. There were two classes used in collecting the data: the experimental group and the control group. This study implemented a quasi experimental as the research method. Furthermore, written test was conducted to obtain the data and students' writing products which were then analyzed using writing assessment criteria taken from Rose (2007, as cited by Emilia, 2011, p.151) . The findings showed that there was a significant difference between the mean of the experimental and that of the control group. The mean of the experimental group (M = 65.7) was higher than the control group (M = 60.8) with the large effect size (r = 0.92). It also showed that t (68) = 2.58 and sig = 0.012, p < 0.05 which means the use of pictures series was effective to improve students' writing skills. It was proved by the students' experimental group significant improvement in genre, register and discourse aspects in the posttest result. This research is expected to contribute to the teaching of English. In addition, it is suggested to investigate the effectiveness of using pictures series in improving other skills. Penelitian ini berjudul " Penggunaan Gambar Berseri Untuk Mengembangkan Kemapuan Siswa Dalam Menulis Teks Prosedur" penelitian ini dilaksanakan untuk menguji keberhasilan penggunaan gambar bereseri untuk mengembangkan kemampuan menulis siswa, khususnya dalam menulis teks prosedur. Peserta dalam penelitian ini adalah siswa dari kelas tujuh di salah satu sekolah menengah pertama di Bandung. Ada dua kelas yang digunakan untuk mengumpulkan data yaitu kelas eksperimen dan kelas kontrol. Penelitian ini menggunakan metode Quasi-experimental. Tes tertulis digunakan untuk mengumpulkan data dan hasil menulis siswa dianalisis menggunakan kriteria penilian khusus yang diambil dari Rose (2007, dalam Emilia, 2011, p.151). Temuan dalam penelitian ini menyatakan bahwa terdapat perbedaan yang cukup signifikan diantara rata-rata nilai grup eksperimen dan grup kontrol. Nilai rata-rata dari grup eksperimen (M = 65.7) lebih tinggi daripada grup kontrol (M = 60.8) dengan ukuran pengaruh yang tinggi (r=0.92). Selain itu terlihat t(68) = 2.58 dan sig = 0.012, p < 0.05 yang berati penggunaan gambar berseri berhasil mengembangkan kemampuan siswa dalam menulis teks prosedur. Itu telah dibuktikan dengan hasil tulisan siswa dari grup eksperiment di posttest yang mendapat perubahan signifikan dari segi Genre, register, dan Discourse. Penelitian ini diharapkan dapat memberikan kontribusi dalam pengajaran bahas inggris. Disarankan untuk meneliti keberhasilan penggunaan gambar berseri dalam mengembangkan kemampuan lainnya.